Nitrogen Fertilizer Regulated Grain Storage Protein Synthesis and Reduced Chalkiness of Rice Under Actual Field Warming - Wang, Xueqin; Wang, Kailu; Yin, Tongyang; Zhao, Yufei; Liu, Wenzhe; Shen, Yingying; Ding, Yanfeng; Tang, She (Frontiers in Plant Science, 2021)
Our previous study has shown that nitrogen plays an important role in dealing with significantly increased chalkiness caused by elevated temperature. However, the role of nitrogen metabolites has not been given sufficient attention, and its regulatory mechanism is not clear. This study investigated the effects of high temperature and nitrogen fertilizer on the synthesis of grain storage protein and further explored the quality mechanism under the actual scenario of field warming. Results showed that increased temperature and nitrogen fertilizer could affect the activities of nitrogen metabolism enzymes, namely, glutamate synthetase, glutamine synthetase, glutamic pyruvic transaminase, and glutamic oxaloacetic transaminase, and the expressions of storage protein synthesis factor genes, namely, GluA and GluB, and subfamily genes, namely, pro14, BiP1, and PDIL1, which co-induced the changes of storage protein synthesis in rice grains. Furthermore, the increased temperature changed the balance of grain storage substances which may lead to the significantly increased chalky rate (197.67%) and chalkiness (532.92%). Moreover, there was a significant negative correlation between prolamin content and chalkiness, indicating that nitrogen fertilizer might regulate the formation of chalkiness by affecting the synthesis of prolamin. Results suggested that nitrogen application could regulate the related core factors involved in nitrogen metabolism pathways, which, in turn, affects the changes in the storage protein components in the grain and further affects quality. Therefore, as a conventional cultivation measure, nitrogen application would have a certain value in future rice production in response to climate warming.